Leadership and crisis management and their link to improvement of hotel performance: A study of the Jordanian hotel sector - Jaaffar A.H.; Alzoubi R.H.; Mohammad Alkharabsheh O.H.; Rajadurai J. (Elsevier Ltd, 2024)
The current environment of volatility, uncertainty, complexity and ambiguity has created a prolonged state of uncertainty for the Jordanian hotel industry. Crisis management leadership is one of the most important attributes for a hotel. The main aim of this study is to evaluate the mediating role of crisis management, the moderating role of a leader's experience, their relationship to styles of leadership (transformational and transactional) and the resultant performance of Jordanian hotels. Research was based on a self-distributed questionnaire survey of 119 respondents currently holding managerial positions in Jordanian 3 to 5 star hotels. Partial Least Square Structural Equation Modelling was then employed. The findings suggest a transformational leadership style and crisis management experience are the most important attributes for a leader to sustain hotel performance during a crisis. Leaders with a transactional leadership style need crisis management skills to sustain hotel performance rather than experience which is not as important in their case. This paper proves that different leadership styles have a different influence on a hotel's survivability during a crisis. Therefore, a hotel's management group must ensure that a leader with an appropriate leadership style takes control during these situations. By combining leadership attributes, experience, and crisis management in a comprehensive framework to ensure sustainable hotel performance in the face of a crisis, this study adds to the body of knowledge on leadership and crisis management practices. 2023 The Authors